Pengaruh Struktur Modal, Pertumbuhan Perusahaan, dan Kebijakan Dividen terhadap Return Saham Perusahaan Manufaktur di BEI Periode 2020-2022 - Anthony Holly; Marselinus Asri; Robert Jao; Alfonsus Jantong; Gregorius Richard Elfegi (Jurnal Ekualisasi, 2026)
The purpose of this research is to analysis the influence of capital structure, company growth and dividend policy on stock return. The data processed in this research are financial reports and annual reports. The population in this study was manufacturing companies, with a total population of 194 companies. The sample in this research was obtained through a purposive sampling method and a sample size of 53 companies was obtained. The data analysis technique used is multiple linear regression analysis. The results of this research show that; capital structure has a negative and significant effect on stock returns, company growth has a positive and significant effect on stock return, and dividend policy has a positive and significant effect on stock return.